Spiritual Leadership in South African - Sirkissoon, Elisha (My University, 2011)
The research problem that this research addresses is to explore and identify the key components of spiritual leadership, within the context of the general concept of leadership, as well as the dynamics between the identified components of spiritual leadership. There is a sense of urgency for humanity to expand their consciousness in order to deal with the challenges arising in organisations and on this planet (Biberman et al, 1999). This includes a need for more holistic leadership that integrates the four aspects of human existence, i.e. the body, mind, heart and spirit (Smith and Rayment, 2007; Moxley, 2000). It is argued that successful corporate leaders of the 21st century will be spiritual leaders, comfortable with their own spirituality and with the knowledge of how to nurture spiritual development in others Cacioppe (2000). The research paradigm adopted in the research was qualitative in nature and takes the form of descriptive study. Fourteen in-depth interviews were conducted using a semi-structured interview questionnaire. The research results show that what underpins the definition of spiritual leadership is the general concept of awareness. The specific results indicate that the components of spiritual leadership include, understanding that one’s position has meaning and purpose; cultivating, embedding and acting with positive spiritual values such as sustainability and cooperation; dissolution of ego; detachment from results; management of stress; growth towards higher states of consciousness; and engaging in reflective practices. The spiritual leader’s responsibility is to constantly strive to refine his/her awareness and that of his/her followers. Engaging in reflective practices, assist in refining and purifying ones consciousness so that this level of awareness can be achieved. The research results did not deviate from literature on spiritual leadership. Much of the literature was reinforced by the results of this research. The implications for this research are manifold; however it is recommended that further empirical studies are conducted, specifically with regards to the business benefits of spirituality in the workplace and factors that constrain the application of spirituality in the workplace.
MBA - WBS
Keywords: Leadership; Spiritual leadership